Comparing the fibrosis inhibition effect of bevacizumab, 5-fluorouracil, and mitomycin C in trabeculectomy in dogs with glaucoma: A series of six cases - Acevedo, Sandra Patricia; Correa Valencia, Nathalia María (Revista Colombiana de Ciencias Pecuarias, 2024)
Anamnesis: A descriptive series of six cases of dogs with glaucoma are presented comparing the fibrosis inhibition effect of three drugs used during trabeculectomy (TEC). Clinical findings: The patients were diagnosed with primary chronic closed-angle glaucoma refractory to topical medical treatment with no pupillary light reflex and negative eyeblink response to threat and ocular pain. Therapeutic approach: Two patients received an intraoperative application of bevacizumab; two received 5-fluorouracil; and two, mitomycin C. Intraocular pressure (IOP) and filtering ampoule were observed on days 1, 7, 30, 60, and 90 post-surgery. Results and conclusion: Bevacizumab regulated IOP under 25 mmHg, constituting the drug of choice for dogs with primary closed-angle glaucoma without previous positive response to topical therapy and subjected to TEC, when compared with 5-fluorouracil and MMC regarding the inhibitory effect of fibrosis.